Profiles of electrostatic potential across the water-vapor, ice-vapor and ice-water interfaces - Bryk, T.; Haymet, A.D.J. (Condensed Matter Physics, 2016)
Ice-water, water-vapor interfaces and ice surface are studied by molecular dynamics simulations with the SPC/E model of water molecules having the purpose to estimate the profiles of electrostatic potential across the interfaces. We have proposed a methodology for calculating the profiles of electrostatic potential based on a trial particle, which showed good agreement for the case of electrostatic potential profile of the water-vapor interface of TIP4P model calculated in another way. The measured profile of electrostatic potential for the pure ice-water interface decreases towards the liquid bulk region, which is in agreement with simulations of preferential direction of motion of Li⁺ and F⁻ solute ions at the liquid side of the ice-water interface. These results are discussed in connection with the Workman-Reynolds effect. Границi роздiлу лiд-вода, вода-пара та поверхня льоду були дослiдженi комп’ютерним моделюванням
методом молекулярної динамiки з SPC/E моделлю молекул води маючи на метi визначити профiлi електростатичного потенцiалу через границi роздiлу фаз. Ми запропонували методологiю для розрахунку
профiлiв електростатичного потенцiалу з використанням пробної частинки. Запропонований пiдхiд показав добре узгодження з профiлем електростатичного потенцiалу для границi роздiлу вода-пара в моделi води, розрахованого iншою методикою. Отриманий профiль електростатичного потенцiалу для чистої
границi роздiлу лiд-вода зменшується в сторону рiдкої фази, що узгоджується з моделюванням переважаючого напрямку руху домiшкових iонiв Li⁺ та ⁻ на рiдиннiй сторонi границi роздiлу лiд-вода. Отриманi
результати обговорюються з точки зору їх вiдношення до ефекту Воркмана-Рейнольдса.